A dynamic model used for controller design of a coal fired once-through boiler-turbine unit. (15th December 2015) - Liu, Ji-Zhen; Yan, Shu; Zeng, De-Liang; Hu, Yong; Lv, You
Abstract: Supercritical OTB (once-through boiler) units with high steam temperature and pressure have been widely used in modern power plants due to their high cycle efficiency and less emissions. To ensure the effective operation of such power generation systems, it is necessary to build a model for the design of the overall control system. There are already detailed models of once-through boilers; however, their complexity prevents them from being applied in the controller design. This study describes a lumped parameter dynamic model that has a relatively low complexity while faithfully capturing the essential overall plant dynamics. The model structure was derived by fundamental physical laws utilizing reasonable simplifications and data analysis to avoid the phase transition position problem. Parameter identification for the model structure was completed using operational data from a 1000 MW ultra-supercritical OTB. The model was determined to be reasonable by comparison tests between computed data and measured data for both steady and dynamic states. The simplified model is verified to have appropriate fidelity in control system design to achieve effective and economic operation of the unit. Highlights: A simplified dynamic model of once-through boiler-turbine unit is given. The essential dynamics of active power and throttle pressure is presented. The change of phase transition position is avoided in modeling process. The model has appropriate complexity and fidelity for controller design.